Individual Reminiscence Therapy can Decrease Depression Level on Elderly at Social Homes - Laily Nur Hidayati; Mustikasari Mustikasari; Yossie Susanti Eka Putri (Jurnal Ners, 2015)
Introduction: Aging is a natural process in oldest old. The psychosocial development of the elderly to enhance self-integration. Reminiscence therapy is one of psychosocial treatment for elderly using memory recall of one’s life event in the past. The purpose of this study was to determine the effect of individual reminiscence therapy on depression among elderly in the social homes.Method: The study design was used Quasy-Eksperiment Pre-Post Test with Control Group. A total of 60 elderly people were recruited in this study and assigned into two groups,  31 participants in the intervention group and 29 participants in the control group. Independent variable was reminiscence therapy five sessions, which given to the intervention group. While, dependent variable was the level of depression on elderly. Data were collected by using GDS, then analyzed by using Wilcoxon and Mann-Whitney statistical test with level of significance α≤0.05.Result: After providing individual reminiscence therapy, the intervention group showed a significant decrease in depression as compared to those in the control group was found (p=0.008).Discussion: The individual reminiscence therapy is useful to overcome depression among elderly. The nurse can know the personality of each elderly so as to improve the quality of nursing care for elderly.